AUDIT OF ACADEMIC SERVICE COMMUNICATION FOR STUDENTS WITH DISABILITIES AT UIN SUNAN KALIJAGA YOGYAKARTA - Maya Sandra Rosita Dewi; Risti Asih; Yani Tri Wijayanti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Academic services for students with disabilities at UIN Sunan Kalijaga Yogyakarta need to be evaluated, especially communication between academic servants and students with disabilities. With the evaluation, communication blockages that interfere with the running of academic services can be identified. Organizational communication studies examine the events or processes of communication implementation can be investigated using communication audits. Communication audit techniques and studies are used to analyze experiences and photograph in the dimension of communicationi. By using qualitative descriptive methods and data collection techniques with the FGD method, the results of this study state that academic service communication for students with disabilities at UIN Sunan Kalijaga is quite good. However, communication blockages were found in some characteristics of students with disabilities. For deaf people with disabilities, they experience problems in communicating because they have to use sign language. For students with visual disabilities, they experience problems with communication media, namely digital media when required to access information through digital media. This study contributes theoretically by applying communication audit in the context of inclusive higher education and practically by offering recommendations to improve accessible academic service systems.